2019
DOI: 10.1021/acs.jpcc.9b09126
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Solution-Processed Organic Memories by Exploiting Synergistic Organic–Inorganic Hybrid Composites

Abstract: Organic−inorganic hybrid composites (HCs) comprising functionalized 2D materials have been given exceptional importance and have been actively employed as memory materials toward development of next-generation resistive memory devices. Herein, we use in situ functionalized rGO−ZnO HC nanofillers for the first time and report the improved memory performances such as a very low operating voltage and a high current ON/OFF ratio along with good repeatability. Hybrid polymer nanocomposite (HPNC) devices were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Log i p = 0.46 × Log V − 4.55 (R 2 = 0.98) (6) As given in Equation ( 1), the slope of the plot is 0.46; slopes of <0.5 indicate a fully diffusion-controlled reaction, while those >0.5 indicate adsorption-controlled reactions [51]. For the current study, the observed slope was 0.46, which confirms the reaction is diffusion-controlled.…”
Section: Influence Of Scan Ratesupporting
confidence: 64%
See 2 more Smart Citations
“…Log i p = 0.46 × Log V − 4.55 (R 2 = 0.98) (6) As given in Equation ( 1), the slope of the plot is 0.46; slopes of <0.5 indicate a fully diffusion-controlled reaction, while those >0.5 indicate adsorption-controlled reactions [51]. For the current study, the observed slope was 0.46, which confirms the reaction is diffusion-controlled.…”
Section: Influence Of Scan Ratesupporting
confidence: 64%
“…The equation of the plot is given in Equation ( 5) with a correlation of 0.99. i p = 30.82 × V 1/2 − 0.29 (R 2 = 0.99) (5) For confirmation of the nature of the electrochemical reaction occurring on the electrode surface, the plot of the logarithm of reduction current response against the logarithm of scan rate was plotted (Figure 4f). The equation of the plot is presented in Equation (6).…”
Section: Influence Of Scan Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, with subsequent increased in applied voltage, greater than the “set” voltage both the light and without light condition, the slope of the MIM curve is of ≈1.0 and 1.1, respectively, shows an ohmic ( I ∝ V ) variation which very clearly observed in Figure 5g,h. [ 54,55 ] During this, all the trap sites are filled and free electron concentration has increased in such a way that they can easily cross the PMMA barriers and reach to the Ag electrode site (presented in Figure 5i). As the barrier is reduced, electrons start to flow from the ITO to the Ag, causing the device switching from OFF to ON state.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this bottleneck and increase the calculation speed of such systems, new electronic equipment needs to be developed. For this purpose, resistive random access memory (RRAM) has several potential advantages over traditional electronic devices, such as higher storage density, better stability, and low power consumption [ 2 , 3 ]. The distinctive characteristic of RRAM is that it has different resistance states under different external voltages, enabling its use in many applications, including storage, neural networks, and general memory for computing.…”
Section: Introductionmentioning
confidence: 99%